+0  
 
0
53
1
avatar

Simplify sqrt{28x} * sqrt{15x} * sqrt{27x}. Express your answer in simplest radical form in terms of x.

 Dec 14, 2021
 #1
avatar+22572 
+1

sqrt(28x) · sqrt(15x) · sqrt(27x)  =  sqrt(4·7x) · sqrt(3·5x) · sqrt(9·3x)

                                                   =  2 · sqrt(7x) · sqrt(3·5x) · 3 · sqrt(3x)

                                                   =  6 · sqrt(7x · 3 · 5x · 3x)

                                                   =  6 · 3 · x · sqrt(7 · 5 · x)

                                                   =  18·x·sqrt(35·x)

 Dec 14, 2021

12 Online Users

avatar